2017
DOI: 10.1002/jctb.5481
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in lactone production from biotransformation of ricinoleic acid based on the porous starch delivery system

Abstract: BACKGROUND The natural gamma‐decalactone (GDL) produced by microbial fermentation is an essential lactone compound as a generally recognized as safe food additive. Effective control of the substrate ricinoleic acid (RA) concentration in the biotransformation medium is a bottleneck for the industrial manufacture of GDL. In this study, porous starch (P‐S) was utilized as a carrier of RA to control its distribution in the medium. The effect of P‐S on the biotransformation was evaluated and the mechanism was revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It is suggested to have a good reusability and potential for industrial application. Recently, Rong et al used a porous starch delivery system to reduce cell damage during the production of γ-decalactone from ricinoleic acid and obtained a product titer of 3.36 g/L . Similalry, Zhang et al used bacterial cellulose-alginate (BC-ALG) composite beads as cell carriers for Y. lipolytica , which increased the yield of γ-decalactone to 8.37 g/L .…”
Section: Factors Affecting γ-Decalactone Accumulation and Related Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested to have a good reusability and potential for industrial application. Recently, Rong et al used a porous starch delivery system to reduce cell damage during the production of γ-decalactone from ricinoleic acid and obtained a product titer of 3.36 g/L . Similalry, Zhang et al used bacterial cellulose-alginate (BC-ALG) composite beads as cell carriers for Y. lipolytica , which increased the yield of γ-decalactone to 8.37 g/L .…”
Section: Factors Affecting γ-Decalactone Accumulation and Related Pro...mentioning
confidence: 99%
“…Recently, Rong et al used a porous starch delivery system to reduce cell damage during the production of γdecalactone from ricinoleic acid and obtained a product titer of 3.36 g/L. 93 Similalry, Zhang et al used bacterial cellulosealginate (BC-ALG) composite beads as cell carriers for Y. lipolytica, which increased the yield of γ-decalactone to 8.37 g/ L. 94 Thus, immobilized cells are significantly more resistant to toxic components in the fermentation system than free cells. Accordingly, the production capacity of strains can be significantly improved by using immobilized cells for microbial fermentation.…”
Section: Engineering the Lactonization Reactionmentioning
confidence: 99%
“…The injector and the detector temperatures were both set as 250°C. The oven temperature was maintained at 120°C for 2 min, increased to 205°C at a rate of 30°C/min, raised to 215°C at a rate of 4°C/min, and increased to 250°C at a rate of 20°C/min and kept stabilized for 3 min. 20 The external standard method was also used for calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Inorganic materials with porous and polymer structure show favorable dispersion and adsorption effect on oily substrate. 18 Our previous experiments showed that expanded vermiculite 19 and porous starch 20 contributed a lot to the distribution of RA, and the yield of GDL increased separately by 50% and 17.5%, respectively. Therefore, we attempt to investigate more functional and low‐cost materials as adsorbent materials (AM) to improve the dispersion of RA.…”
Section: Introductionmentioning
confidence: 98%
“…This approach allowed to achieve a GDL titer of 8.05 g L −1 . Later in 2017, GDL production from RA by Y. lipolytica has been improved by a porous starch delivery system (Rong et al 2017a). This system simultaneously acted as dispersant to control RA release and a lactone adsorbent, which significantly decreased the risk of cell damage.…”
Section: Lactonesmentioning
confidence: 99%